No milk for the bear: the impact on the Baltic states of Russia's counter-sanctions - Kaspar Oja (Baltic Journal of Economics, 2015)
The Russian government banned in August 2014 imports of different food and agricultural products from the European Union as a countermeasure to sanctions introduced by the EU and several other countries after Russia's actions in Ukraine and the annexation of Crimea. This paper assesses the effect of Russia's counter-sanctions on the economies of the Baltic states using different statistics sources and an international input–output model, while taking into account possible data problems in international trade data due to re-exports. The amount of trade affected by Russia's counter-sanctions varies across the Baltic states. In 2013, the exports of goods affected amounted to 2.6% of GDP in Lithuania, 0.4% of GDP in Estonia, and 0.3% of GDP in Latvia, but re-exports are included in these numbers. The overall impact of the sanctions on GDP once intra-EU supply chains are taken into account is below 0.5% of GDP in all the Baltic states.
Keywords: F47; F51; L66; Q17; 330; EU; Russia; sanctions; international trade; economic impact